Flip-flop girl - Paterson, Katherine (New York : Puffin, 1996)
Uprooted following the death of their father, nine-year-old Vinnie and her five-year-old brother, Mason, cope in different ways--one in silence--but both with the help of Lupe, the flip-flop girl.
5.4
3-6
3-6
Wilson's Children
Wilson's Junior High School
Elem. School Library Collection
Keywords: Brothers and sisters -- Fiction; Grief -- Fiction; Death -- Fiction; Friendship -- Fiction; Selective mutism -- Fiction; Moving, Household -- Fiction; Siblings -- Fiction; Grief -- Fiction; Death -- Fiction; Friendship -- Fiction; Mutism -- Fiction; Moving -- Fiction